2013
DOI: 10.1111/1467-8489.12027
|View full text |Cite
|
Sign up to set email alerts
|

Valuing quality attributes of Australian merino wool

Abstract: We measure the relationship between clean prices of individual lots of wool sold at auction and a range of characteristics of the raw wool. Based on the data for 111,440 fleece lots sold in the 2008-2009 auction season, five hedonic models are estimated to determine the premiums and discounts associated with each wool characteristic in five micron categories. Several wool characteristics exhibited significant nonlinear relationships, and therefore, joint density functions were assessed where appropriate. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Similar results from several scholars were observed by several scholars, such as Erasmus and Delport (1987), Pepper et al (2000), Gibbon and Nolan (2011), Nolan et al (2013), Nolan (2014) and Scobie et al (2015), who found that fibre diameter has the greatest influence on the Merino wool price. The sizes of wool fibres are described by the diameter of wool fibres (Das et al, 2015).…”
Section: Rjtasupporting
confidence: 87%
“…Similar results from several scholars were observed by several scholars, such as Erasmus and Delport (1987), Pepper et al (2000), Gibbon and Nolan (2011), Nolan et al (2013), Nolan (2014) and Scobie et al (2015), who found that fibre diameter has the greatest influence on the Merino wool price. The sizes of wool fibres are described by the diameter of wool fibres (Das et al, 2015).…”
Section: Rjtasupporting
confidence: 87%
“…The fiber diameter is an important raw wool characteristic because it is a significant determinant of greasy wool price, and there is a premium paid for finer wool types ( Nolan et al, 2014 ). The effects of DDGS inclusion were not detected on fiber diameter but quadratically increased ( P = 0.04) SD fiber diameter, with the highest SD in the 25DDGS experimental group ( Table 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…() and Todd and Cowell () in the cattle industry and Nolan et al . () in the wool industry. There are two related lines of the hedonic pricing approach.…”
Section: Hedonic Pricing Theorymentioning
confidence: 99%